2006
DOI: 10.1097/01.pas.0000202048.28203.25
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Prognostic Significance of Mitotic Index Using the Mitosis Marker Phospho-histone H3 in Low and Intermediate-grade Infiltrating Astrocytomas

Abstract: Distinguishing between grade II and grade III diffuse astrocytomas is important both for prognosis and for treatment decision-making. However, current methods for distinguishing between grades based on proliferative potential are suboptimal, making identification of clear cutoffs difficult. In this study, we compared the results from immunohistochemical staining for phospho-histone H3 (pHH3), a specific marker of cells undergoing mitosis, with standard mitotic counts (number of mitoses/10 high-power fields) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
113
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(126 citation statements)
references
References 21 publications
10
113
2
1
Order By: Relevance
“…[1,2] Colman et al [3,4] studied PHH3 staining with MIB1 and found that the combination of both with regard to grade and prognosis was better which is concordant with our study, in which 36 glial tumors were positive for GFAP with PHH3 and corresponding Ki67 staining; however, the gemistocytic glioblastoma was negative for GFAP.…”
Section: Discussionsupporting
confidence: 80%
“…[1,2] Colman et al [3,4] studied PHH3 staining with MIB1 and found that the combination of both with regard to grade and prognosis was better which is concordant with our study, in which 36 glial tumors were positive for GFAP with PHH3 and corresponding Ki67 staining; however, the gemistocytic glioblastoma was negative for GFAP.…”
Section: Discussionsupporting
confidence: 80%
“…Therefore, apart from being a time-consuming exercise, assessment of mitotic figures in 50 high-power fields is often poorly reproducible among observers. Phospho-histone H3 immunostaining has been demonstrated to specifically detect mitotic figures in several human tumors 19,22,27,[30][31][32] but has never been tested in adrenocortical carcinomas, so far. This is surprising, as it is well known that the recognition of this tumor type largely relies on mitotic index evaluation, as one of the nine factors included in the Weiss Score 1 or in other diagnostic algorithms.…”
Section: Phospho-histone H3 Role To Highlight Mitotic Figures As a DImentioning
confidence: 99%
“…11,12 Phospho-histone H3 immunostaining has been shown to be a reliable and easy method for mitotic index evaluation in melanoma, with both diagnostic [13][14][15][16][17][18] and prognostic 17,[19][20][21] implications. Moreover, it has been also successfully applied in different neoplasms of the breast, [22][23][24][25][26] meninges, [27][28][29] brain, 30 lung, 31 soft tissues, [32][33][34] esophagus, 35 female genital tract, 36,37 prostate, 38 and urothelium, 39 as well as in cytology material from pancreatic endocrine tumors 40 and urothelial carcinoma. 41 The Ki-67 index represents an alternative method for assessing the proliferative potential in adrenocortical tumors and has already been shown to differentiate adrenocortical adenoma from carcinoma, [42][43][44][45][46][47][48][49] and to predict tumor behavior.…”
mentioning
confidence: 99%
“…Thus, immunodetection of phosphohistone H3 has become a sensitive and specific marker of mitotic figures and correlates with outcome in a variety of different human tumor types, 9 including breast carcinoma, 10,11 colorectal adenocarcinoma, 12 ovarian serous adenocarcinoma, 13 pulmonary neuroendocrine carcinoma, 14 uterine smooth muscle tumors, 15 astrocytomas, 16 and meningiomas. 17 In melanoma, immunodetection of phosphohistone H3 has been shown to increase the sensitivity and accuracy for mitotic figure detection; it improves inter-observer variability; and it reduces the time required to identify mitoses in primary cutaneous and uveal melanomas.…”
mentioning
confidence: 99%